2021
DOI: 10.3390/vaccines9121391
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Vaccine Literacy, Vaccine Perception and Vaccine Hesitancy on Israeli Parents’ Acceptance of the COVID-19 Vaccine for Their Children: A Cross-Sectional Study

Abstract: Vaccination is currently the most effective strategy for combating COVID-19. COVID-19 vaccines were introduced to the adult population in Israel in early December 2020 and have been available for children aged 12–15 since June 2021. Our study aimed at assessing the influence of vaccine literacy, perception, hesitancy, and behavior on Israeli parents’ intentions to have their children vaccinated. Using an anonymous online questionnaire, we recruited 520 parents; 70.4% of the parents indicated that they would ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 36 publications
5
65
1
1
Order By: Relevance
“…Among parents who themselves were vaccinated, the unadjusted odds of vaccine uptake for their older child were 14 times higher than unvaccinated parents. Our findings are consistent with previous research reporting that vaccinated parents are more likely than unvaccinated parents to accept the vaccine for their children ( 6 , 8 – 10 , 12 , 16 , 17 , 19 , 21 , 22 ). Further, our data point to the influence of one's larger social context on vaccine acceptance.…”
Section: Discussionsupporting
confidence: 93%
“…Among parents who themselves were vaccinated, the unadjusted odds of vaccine uptake for their older child were 14 times higher than unvaccinated parents. Our findings are consistent with previous research reporting that vaccinated parents are more likely than unvaccinated parents to accept the vaccine for their children ( 6 , 8 – 10 , 12 , 16 , 17 , 19 , 21 , 22 ). Further, our data point to the influence of one's larger social context on vaccine acceptance.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study of physicians in a university-based teaching hospital in Thailand found that better VL was inversely related to VH (aOR 0.34; 95% CI 0.13-0.9; p = 0.029) [22]. Parents with higher VL preferred to vaccinate their children compared to those with lower VL [29]. This is implying the role of VL in reducing VH and increasing AV.…”
Section: Discussionmentioning
confidence: 77%
“… Yes [Y], unsure [U], no [N] Yes: 70 Unsure: NR No: NR ( Evans et al, 2021 ) If a COVID-19 vaccine is available, will you vaccinate for your child? Yes [Y], unsure [U], no [N] Yes: 48 Unsure: 38 No: 14 ( Gendler and Ofri, 2021 ) If a vaccine against COVID-19 is available, how likely would you be to get your children vaccinated? Very likely [Y], somewhat likely [Y], somewhat unlikely [N], definitely not [N] Yes: 70.4 No:29.6 ( Humble et al, 2021 ) If a safe and effective COVID-19 vaccine is available, I will get my child/children vaccinated Strongly agree [Y], agree [Y], neutral [U], disagree [N], strongly disagree [N] Yes: 63.1 Unsure: NR No: NR ( Kezhong et al, 2021 ) If a COVID-19 vaccine is available, will you vaccinate for your child?…”
Section: Resultsmentioning
confidence: 99%